2006
DOI: 10.1529/biophysj.105.074690
|View full text |Cite
|
Sign up to set email alerts
|

First Steps of Retinal Photoisomerization in Proteorhodopsin

Abstract: The early steps (<1 ns) in the photocycle of the detergent solubilized proton pump proteorhodopsin are analyzed by ultrafast spectroscopic techniques. A comparison to the first primary events in reconstituted proteorhodopsin as well as to the well known archaeal proton pump bacteriorhodopsin is given. A dynamic Stokes shift observed in fs-time-resolved fluorescence experiments allows a direct observation of early motions on the excited state potential energy surface. The initial dynamics is dominated by sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
140
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(165 citation statements)
references
References 43 publications
22
140
1
Order By: Relevance
“…The transient spectrum at the end of the investigated time range (1.5 ns) exhibits a red-shifted positive photoproduct difference band around 510 nm, which is indicative of the formation of the K intermediate in retinal proteins. [16,18,25,27,49] This difference pattern shows the same spectral signature as that observed in early transient spectra of flash photolysis measurements. [10] Low-temperature FTIR spectroscopy revealed that the retinal in the K state of ChR-2 underwent an all-trans to 13-cis isomerization.…”
Section: Ultrafast Excited-state Deactivationsupporting
confidence: 73%
“…The transient spectrum at the end of the investigated time range (1.5 ns) exhibits a red-shifted positive photoproduct difference band around 510 nm, which is indicative of the formation of the K intermediate in retinal proteins. [16,18,25,27,49] This difference pattern shows the same spectral signature as that observed in early transient spectra of flash photolysis measurements. [10] Low-temperature FTIR spectroscopy revealed that the retinal in the K state of ChR-2 underwent an all-trans to 13-cis isomerization.…”
Section: Ultrafast Excited-state Deactivationsupporting
confidence: 73%
“…The protein was eluted in 50 mM Tris, 100 mM NaCl, 300 mM imidazole, 1 mM dithiothreitol, pH 7.6, and exchanged into 10 mM HEPES, 0.05% (w/v) b-DDM, pH 7.6 using spin dialysis membranes (40K MWCO). Purity of the resulting pR was analyzed by SDS-PAGE, and concentration was calculated using the absorbance value at 520 nm and an extinction coefficient of 45,000 M -1 cm -1 (19); pure fractions were stored at 4 C for up to 2 months. The typical protein yields were in the range of 1-2 mg of pR per liter of culture.…”
Section: Plasmids and Strainsmentioning
confidence: 99%
“…Because the scattering from intact proteoliposomes obscures the pR absorption, we first used a 10% (w/v) aqueous solution of Triton X-100 to break apart the liposomes and incorporate the protein into detergent micelles. FITC-a-HSVand pR concentrations were then determined using absorbance values at 494 nm and 520 nm, respectively, and extinction coefficients of 70,000 M -1 cm -1 and 45,000 M -1 cm -1 , respectively (19).…”
Section: Zeta Potential Measurementsmentioning
confidence: 99%
“…At pH 6, where the Schiff base counterion Asp97 is protonated, the reaction is less efficient, probably due to the altered charge distribution in the retinal pocket. 8,9,16 However, the reaction mechanism is not altered by the pH of the environment, and the transient absorption data of pR in alkaline and acidic environment can be interpreted using the same model for the dynamics of the isomerization. 9 Although the excited state evolution of retinal in proteorhodopsin has been characterized, more information on what determines the quantum yield of its photoisomerization can be obtained from monitoring the relative progress on the excited state potential and looking at the dynamics on the ground state potential energy surface, using pump-dump-probe spectroscopy.…”
Section: Introductionmentioning
confidence: 99%